Recovery of State Losses Through the Economic Analysis of Law Approach: Pemulihan Kerugian Negara Melalui Pendekatan Economic Analysis of Law - Octavianus, Dwi Caesar; Rato, Dominikus; Anggono, Bayu Dwi (Universitas Muhammadiyah Sidoarjo, 2023)
In the era of globalization, addressing the complex challenges of state financial recovery due to corruption and illicit practices necessitates a holistic approach that integrates legal, economic, and social aspects. This research employs normative research methods and a conceptual approach to analyze the legal framework and economic concepts related to the Economic Analysis of Law (EAL) in the context of national financial recovery. By synthesizing legal and economic principles, the study demonstrates that EAL proves highly effective in confronting the challenges of state financial recovery. The integration of economic principles in legal analysis allows governments to craft policies that are not only legally robust but also economically efficient. Through a focused examination of the economic impact of illegal actions on state finances, EAL facilitates the identification of losses and the design of precise recovery strategies. The findings underscore the potential of EAL as a valuable tool for governments worldwide in formulating sustainable policies for financial restitution.Highlights: Holistic Approach: The study advocates for a holistic approach to state financial recovery by integrating legal and economic perspectives, emphasizing the interconnectedness of legal principles and economic efficiency. Efficient Policy Design: Economic Analysis of Law (EAL) is shown to be a powerful tool in crafting policies that are not only legally robust but also economically efficient, ensuring a balanced and effective strategy for financial restitution. Focused Impact Analysis: EAL's focus on analyzing the economic impact of illicit actions aids governments in accurately identifying financial losses, enabling the precise design of recovery strategies and contributing to more targeted and effective recovery efforts. Keywords: Economic Analysis of Law, State Financial Recovery, Legal and Economic Integration, Illicit Practices, Policy Formulation